2020
DOI: 10.1002/ana.25749
|View full text |Cite
|
Sign up to set email alerts
|

Nimodipine Reduces Dysfunction and Demyelination in Models of Multiple Sclerosis

Abstract: Objective Treatment of relapses in multiple sclerosis (MS) has not advanced beyond steroid use, which reduces acute loss of function, but has little effect on residual disability. Acute loss of function in an MS model (experimental autoimmune encephalomyelitis [EAE]) is partly due to central nervous system (CNS) hypoxia, and function can promptly improve upon breathing oxygen. Here, we investigate the cause of the hypoxia and whether it is due to a deficit in oxygen supply arising from impaired vascular perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…Similarly, a mutation in the microglial TREM2 receptor (an AD susceptibility gene) that increases the production of inflammatory mediators also leads to a decrease of CBF [85]. The neuroinflammation occurring in multiple sclerosis can also be associated with hypoperfusion that is correctable by blocking ET A receptors or voltage-gated calcium channels [33,34]. Schematic diagram showing how the amyloid beta and tau cascades can be initiated from two entry points (red boxes): (i) a decrease of cerebral blood flow (CBF) which lowers brain O 2 and glucose and thus upregulates the enzyme (BACE1) that makes Aβ or (ii) an increase in Aβ level due to more production or less clearance of Aβ.…”
Section: Mechanism Of Cbf Decreasementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a mutation in the microglial TREM2 receptor (an AD susceptibility gene) that increases the production of inflammatory mediators also leads to a decrease of CBF [85]. The neuroinflammation occurring in multiple sclerosis can also be associated with hypoperfusion that is correctable by blocking ET A receptors or voltage-gated calcium channels [33,34]. Schematic diagram showing how the amyloid beta and tau cascades can be initiated from two entry points (red boxes): (i) a decrease of cerebral blood flow (CBF) which lowers brain O 2 and glucose and thus upregulates the enzyme (BACE1) that makes Aβ or (ii) an increase in Aβ level due to more production or less clearance of Aβ.…”
Section: Mechanism Of Cbf Decreasementioning
confidence: 99%
“…Similarly, a mutation in the microglial TREM2 receptor (an AD susceptibility gene) that increases the production of inflammatory mediators also leads to a decrease of CBF [ 85 ]. The neuroinflammation occurring in multiple sclerosis can also be associated with hypoperfusion that is correctable by blocking ET A receptors or voltage-gated calcium channels [ 33 , 34 ].…”
Section: Mechanism Of Cbf Decreasementioning
confidence: 99%
“…Investigations indicated that the hypoxia was caused by insufficient perfusion of the CNS, creating a shortage of oxygen delivery in the inflamed area ( 54 ). Accordingly, it was found that therapeutic approaches aimed at alleviating hypoxia, with inspired oxygen, or alleviating hypoperfusion, with vasodilating agents, were related to improved neurologic outcome and reduced later stage demyelination in the affected animals ( 17 ). These findings suggest that hypoxia and hypoperfusion may render nerve cells inexcitable through depolarization, causing disability in the acute stage, but also damage oligodendrocytes, causing subsequent demyelination.…”
Section: Octa In Neuroinflammatory Diseasementioning
confidence: 99%
“…However, if vascular density loss occurs after thinning of retinal layers, this suggests that vascular supply may be reduced due to lower local metabolic demand. This is an important question, given the potential therapeutic possibilities that may reduce MS disability accrual by alleviating hypoperfusion, that OCTA might help answer ( 17 ).…”
Section: Future Outlookmentioning
confidence: 99%
See 1 more Smart Citation